Molluscan Evidence for Slow Subsidence in the Bobotsari Basin during the Plio-Pleistocene, and Implications for Petroleum Maturity - Aswan, Aswan; Zaim, Yahdi; Rizal, Yan; Prasetyo, Unggul (Journal of Mathematical and Fundamental Sciences, 2015)
Integrated studies of the stratigraphy, sedimentology and molluscan paleontology of several late Neogene localities in West and Central Java (Indonesia) showed that deposition took place under marine conditions until early in the Pleistocene in the Bobotsari Basin. In contrast, in the adjacent Bogor and North Serayu basins deposition was terrestrial (fluviatile) during the Pleistocene, as subsidence had ceased. Our interpretation is based mainly on the marine mollusks present in the Plio-Pleistocene Bantardawa-Talanggudang Formation in the Bobotsari Depression. This interpretation is supported by seismic analyses and by age determinations based on planktonic foraminifers. We concluded that slow tectonic subsidence continued in the Bobotsari Depression until the early Pleistocene. Slow, long-continued subsidence in the Bobotsari Basin had a significant impact on hydrocarbon maturity compared to that of adjacent basins. We interpret the high total organic carbon (TOC) in the geochemical analyses of samples from Bobotsari Neogene outcrops as resulting from rapid burial in the Bobotsari Basin and slow subsidence continuing into the early Pleistocene.